Polymer Waveguide Sensor Based on Evanescent Bragg Grating for Lab-on-a-Chip Applications - Zhenyu Zhang; Ahmad Abdalwareth; Günter Flachenecker; Martin Angelmahr; Wolfgang Schade (Sensors, 2024)
In this work, an evanescent Bragg grating sensor inscribed in a few-mode planar polymer waveguide was integrated into microchannel structures and characterized by various chemical applications. The planar waveguide and the microchannels consisted of epoxide-based polymers. The Bragg grating structure was postprocessed by using point-by-point direct inscription technology. By monitoring the central wavelength shift of the reflected Bragg signal, the sensor showed a temperature sensitivity of −47.75 pm/K. Moreover, the functionality of the evanescent field-based measurements is demonstrated with two application examples: the refractive index sensing of different aqueous solutions and gas-phase hydrogen concentration detection. For the latter application, the sensor was additionally coated with a functional layer based on palladium nanoparticles. During the refractive index sensing measurement, the sensor achieved a sensitivity of 6.5 nm/RIU from air to 99.9% pure isopropyl alcohol. For the gas-phase hydrogen detection, the coated sensor achieved a reproducible concentration detection up to 4 vol% hydrogen. According to the reported experimental results, the integrated Bragg-grating-based waveguide sensor demonstrates high potential for applications based on the lab-on-a-chip concept.